2006
DOI: 10.1063/1.2191428
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the acoustic radiation strain in solids

Abstract: Measurements of the static displacement induced by the radiation stress associated with a longitudinal acoustic wave propagating in a solid are presented. Acoustic tone bursts were launched into fused silica and duraluminum samples. The static displacement was measured at the sample free surface with an optical interferometer. The role of the nonlinearity parameter and the variations of the dc pulse amplitude with the acoustic energy confirm results obtained by other authors. However, our conclusions on the dc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 5 publications
3
38
0
Order By: Relevance
“…Several recent studies have used the acoustic-radiationinduced strain to measure the acoustic nonlinearity parameter. [1][2][3][4][5][6] It is well known that the acoustic-radiation-induced strain is related directly to the static term in the displacement. However, there has been some confusion in the literature regarding the magnitude of the static term in the displacement solution to the nonlinear equation.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have used the acoustic-radiationinduced strain to measure the acoustic nonlinearity parameter. [1][2][3][4][5][6] It is well known that the acoustic-radiation-induced strain is related directly to the static term in the displacement. However, there has been some confusion in the literature regarding the magnitude of the static term in the displacement solution to the nonlinear equation.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those recently published in the case of a solid. 16 A discussion about the pressure associated to the quasi-static part of the LF displacement is presented in Sec. III.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…Narasimha et al 7 conducted similar experiments in Al7175-T7351 alloy using a piezoelectric receiver and confirmed that the detected quasistatic pulse exhibited a flat-top shape and its amplitude was independent of the duration of the tone burst. In response, Cantrell 8 argued that the experimental results of Jacob et al 5 were the spurious consequence of uncorrected diffraction and attenuation effects in their measurements and suggested that the results of Narasimha et al 7 were a consequence of the characteristics of their receiving transducer.…”
Section: Introductionmentioning
confidence: 97%
“…Later on, additional experimental, computational, and analytical evidence emerged which shows that Yost and Cantrell's prediction of a right-triangular shape for the quasistatic displacement pulse cannot be independently verified. Jacob et al 5 conducted displacement measurements with an optical interferometer in fused silica and aluminum alloy samples and found that the quasistatic displacement pulse produced by a longitudinal acoustic wave exhibited a flat-top shape with amplitude independent of the duration of the tone burst, but proportional to the propagation distance. R enier et al 6 also found that the amplitude of the quasistatic displacement generated by an ultrasonic tone burst propagating through water was linearly proportional to the propagation distance.…”
Section: Introductionmentioning
confidence: 98%